BIOPHILIC DESIGN PATTERNS: Emerging Nature-Based Parameters for Health and Well-Being in the Built Environment - Ryan, Catherine O.; Browning, William D; Clancy, Joseph O; Andrews, Scott L; Kallianpurkar, Namita B (ArchNet-IJAR, 2014)
This paper carries forth the conceptual framework for biophilic design that was first laid out by Cramer and Browning in Biophilic Design (2008), which established three categories meant to help define biophilic buildings – Nature in the Space, Natural Analogues and Nature of the Space – and a preliminary list of “biophilic conditions”. New research and insights from the neurosciences, endocrinology and other fields have since helped evolve the scientific basis for biophilic design. This paper begins to articulate this growing body of research and emerging design parameters in architectural terms, so that we may draw connections between fields of study, highlight potential avenues for future research, evolve our understanding of biophilic design patterns, and capture the positive psychophysiological and cognitive benefits afforded by biophilia in our design interventions.